The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.2993/0278-0771-35.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Disturbing Developments: An Archaeobotanical Perspective on Pinyon-Juniper Woodland Fire Ecology, Economic Resource Production, and Ecosystem History

Abstract: It has long been thought that the only means by which the American Southwest's extensive pinyon-juniper woodlands, with their inherently low primary productivity, could have supported indigenous populations during prehispanic times was with the transformative consequences associated with the widespread cultivation of low-moisture-intolerant domesticated plants, principally maize (Zea mays L.). In this paper we present an alternative to this orthodox view which posits that anthropogenic fire was a vegetation-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…The cereals identified in the K pits, emmer wheat ( Triticum dicoccum ) and six-row barley ( Hordeum vulgare ), are dry adapted and capable of being grown with limited rainfall, although it is unclear whether precipitation sufficient for rainfall agriculture would have been present in the Fayum even during the early and middle Holocene (Hassan, 1986: 494; Phillipps et al, 2012; Wendrich et al, 2017). As a result, it has been suggested that agriculture in the Fayum took place either at the lakeshore following seasonal recession of the Nile-flood-fed high lake stand (Caton-Thompson and Gardner, 1934; Wenke and Casini, 1989: 147–148; Wenke et al, 1988) or in wadis that channeled winter rains to strategically planted areas (Holdaway et al, 2016: 6), analogous to desert production strategies for maize and other crops in the American Southwest (Fish and Fish, 1992; Fish et al, 1985; Sullivan, 2000; Sullivan et al, 2015). Wood charcoal can distinguish whether basin- or lakeshore thickets were cleared for agriculture, suggesting an agricultural strategy in seasonally inundated soils or whether wood from wadis was cleared and brought to settled locations for fuel, indicating a rainfed agricultural strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The cereals identified in the K pits, emmer wheat ( Triticum dicoccum ) and six-row barley ( Hordeum vulgare ), are dry adapted and capable of being grown with limited rainfall, although it is unclear whether precipitation sufficient for rainfall agriculture would have been present in the Fayum even during the early and middle Holocene (Hassan, 1986: 494; Phillipps et al, 2012; Wendrich et al, 2017). As a result, it has been suggested that agriculture in the Fayum took place either at the lakeshore following seasonal recession of the Nile-flood-fed high lake stand (Caton-Thompson and Gardner, 1934; Wenke and Casini, 1989: 147–148; Wenke et al, 1988) or in wadis that channeled winter rains to strategically planted areas (Holdaway et al, 2016: 6), analogous to desert production strategies for maize and other crops in the American Southwest (Fish and Fish, 1992; Fish et al, 1985; Sullivan, 2000; Sullivan et al, 2015). Wood charcoal can distinguish whether basin- or lakeshore thickets were cleared for agriculture, suggesting an agricultural strategy in seasonally inundated soils or whether wood from wadis was cleared and brought to settled locations for fuel, indicating a rainfed agricultural strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive natural forest fires are infrequent in this area today, and probably the same was true in the past, because juniper and pinyon plants are widely spaced [ 54 ] and the fuel to support a spreading crown fire is generally not present [ 55 ]. Furthermore, there is evidence that the ancient cultures of the American Southwest undertook periodic low-intensity burning which may have protected the forests from crown fires [ 56 ] as well as improve forage for game [ 34 ]. Lightning strikes do occur, but these are generally limited to the struck tree [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data do not include counts of indirect indicators of plant use, such as cone scales, seed coats, nutshell, bark, needles, stems, leaves, wood, or cupules. This method was selected because it tightly constrains frequencies of edible plant parts—seeds or nuts—that in all likelihood were the objects of wild plant cultivation, wild plant gathering, or domesticated plant cultivation (Sullivan et al 2015:44). Ubiquity values are given in parentheses.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the Upper Basin is blanketed by a dense pinyon-juniper woodland (Vankat 2013) that becomes intermixed with ponderosa pine on its western edge but grades to grassland farther south (Darling 1967). Like so many areas in the upland Southwest occupied between AD 875 and 1200 (Euler 1988), the Upper Basin is thickly stocked with abandoned one- to two-room structures and other features, such as rock alignments and terraces (Sullivan et al 2015), which conventionally have been interpreted as landscape signatures of maize production (e.g., Effland et al 1981; Stewart and Donnelly 1943). However, these appearances are deceiving when we examine the area's modern and ancient environmental characteristics and its archaeo-economic record and evaluate the extent to which they align with the attributes of maize-based foodways.…”
Section: Suitability Of the Upper Basin For Maize-based Foodwaysmentioning
confidence: 99%
See 1 more Smart Citation